A bulk segregant transcriptome analysis reveals metabolic and cellular processes associated with Orange allelic variation and fruit β-carotene accumulation in melon fruit. Issue 1 (December 2015) - Chayut, Noam; Yuan, Hui; Ohali, Shachar; Meir, Ayala; Yeselson, Yelena; Portnoy, Vitaly; Zheng, Yi; Fei, Zhangjun; Lewinsohn, Efraim; Katzir, Nurit; Schaffer, Arthur; Gepstein, Shimon; et al.
Abstract Background Melon fruit flesh color is primarily controlled by the "golden" single nucleotide polymorhism of the"Orange" gene, CmOr, which dominantly triggers the accumulation of the pro-vitamin A molecule, β-carotene, in the fruit mesocarp. The mechanism by whichCmOr operates is not fully understood. To identify cellular and metabolic processes associated withCmOr allelic variation, we compared the transcriptome of bulks of developing fruit of homozygous orange and green fruited F3 families derived from a cross between orange and green fruited parental lines. Results Pooling together F3 families that share same fruit flesh color and thus the sameCmOr allelic variation, normalized traits unrelated toCmOr allelic variation. RNA sequencing analysis of these bulks enabled the identification of differentially expressed genes. These genes were clustered into functional groups. The relatively enriched functional groups were those involved in photosynthesis, RNA and protein regulation, and response to stress. Conclusions The differentially expressed genes and the enriched processes identified here by bulk segregant RNA sequencing analysis are likely part of the regulatory network ofCmOr . Our study demonstrates the resolution power of bulk segregant RNA sequencing in identifying genes related to commercially important traits and provides a useful tool for better understanding the mode of action ofCmOr gene in the mediation of carotenoid accumulation.